Revised Guidelines for Public Debt Management. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The Guidelines for Public Debt Management (Guidelines) have been developed as part of a broader work program undertaken by the IMF and the World Bank to strengthen the international financial architecture, promote policies and practices that contribute to financial stability and transparency, and reduce countries' external vulnerabilities. In developing the Guidelines, IMF and World Bank staffs worked in close collaboration with debt management entities from a broad group of IMF-World Bank member countries and international institutions in a comprehensive outreach process. The debt managers' insights, which this process brought to the Guidelines, have enabled the enunciation of broadly applicable principles, as well as institutional and operational foundations, that have relevance for members with a wide range of institutional structures and at different stages of development. The revision of the Guidelines was requested by the G-20 Finance Ministers and Central Bank Governors, at their meeting in Moscow, on February 15-16, 2013. Since their adoption in 2001, and amendments in 2003, financial sector regulatory changes and macroeconomic policy developments, especially in response to the recent financial crisis, have significantly affected the general financial landscape. As a consequence, many countries have experienced significant shifts in their debt portfolios, in terms of both size and composition. Accordingly, the Guidelines were reviewed and revised to reflect the evolving public debt management challenges over the last decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet